By how much did the Malawi economic crisis affect the welfare of the people? : evidence from survey data - Mussa, Anwar (School of Economics, 2016)
The study uses data from the Malawi Integrated Household Panel Sur- vey (IHPS) to investigate the impact of the late 2011 through 2012 economic crisis in Malawi on the well-being of the people. Empirical results show that there was no statistically significant decline in the standard of living across Malawi between 2010 and 2013. The poverty incidence levels across areas in Malawi remained at their 2010 levels except for rural-south which experienced a significant decline in the number of poor people in 2013. Stochastic dominance test results show that irrespective of the choice of poverty measure and poverty line, there was no significant change in poverty between the two years save for rural areas in the northern and southern regions of Malawi. These areas actually experi- enced welfare gains, hence a decline in poverty. Sectoral decomposition results indicate that within area changes in poverty incidence, depth and severity contributed heavily to the overall change in poverty as opposed to population movements between rural and urban areas as well as among rural areas in the three regions of Malawi (north, centre and south).